1979
DOI: 10.3758/bf03209649
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of predatory behaviors in laboratory mice following lithium chloride injections or electric shock

Abstract: Screening and Punishment Trials On Day 4, each mouse was exposed to a cricket which was taped to a wall in the shuttle cage, The cricket's hind legs were taped to its body, The cricket was then taped to the wall such

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…After four trials, we were unable to show conditioning against the food resource and submit that substantial logistical, animal care, and maintenance issues, and variation in wolf response to the electronic collar complicates application of this type of aversive conditioning into management programs. Furthermore, difficulty in producing aversions to consumptive behavior has been observed (Garcia & Koelling 1966), although other researchers showed that reduction of consumptive behaviors using electrical stimuli is possible (Krane & Wagner 1975; Klunder & O'Boyle 1979). Linhart et al (1976) and Andelt et al (1999) demonstrated the effectiveness of electronic training collars for minimizing attack behavior from coyotes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After four trials, we were unable to show conditioning against the food resource and submit that substantial logistical, animal care, and maintenance issues, and variation in wolf response to the electronic collar complicates application of this type of aversive conditioning into management programs. Furthermore, difficulty in producing aversions to consumptive behavior has been observed (Garcia & Koelling 1966), although other researchers showed that reduction of consumptive behaviors using electrical stimuli is possible (Krane & Wagner 1975; Klunder & O'Boyle 1979). Linhart et al (1976) and Andelt et al (1999) demonstrated the effectiveness of electronic training collars for minimizing attack behavior from coyotes.…”
Section: Discussionmentioning
confidence: 99%
“…Attack and kill behaviors are separate and distinct from consumption behaviors for predation management (Klunder & O'Boyle 1979; Sterner 1995). However, because experimental evaluations of depredation control technologies are difficult to implement in actual management situations, we tested two repellents for their efficacy in reducing consumption only.…”
Section: Methodsmentioning
confidence: 99%